Health related quality of life and its predictors among postpartum mother in Southeast Ethiopia: A cross-sectional study - Degefa Gomora; Chala Kene; Ayinamaw Embiale; Yohannes Tekalegn; Girma Geta; Kenbon Seyoum; Girma Beressa; Daniel Atlaw; Biniyam Sahiledengle; Fikreab Desta; Neway Ejigu; Usman Hussein; et al. (Heliyon, 2024)
Background: Post-childbirth, woman's health-related quality of life (HRQOL) is significantly impacted, leading to decreased daily activity, reduced self-care, challenges with breastfeeding and baby weaning, and increased medical costs for both mother and newborn.This study aimed to assess the HRQOL and its predictors among postpartum women in Southeast Ethiopia. Methods: A cross-sectional study was conducted in Southeast Ethiopia between March and May 2022, involving randomly selected sample of 794 postpartum women attending immunization services in public health facilities. Data was collected using a validated questionnaire, and descriptive statistics were computed. A bivariable and multivariable logistic regression model was fitted to predict HRQOL, with odds ratios and 95% confidence intervals used to estimate associations. Results: The study revealed that the overall HRQOL, physical component summary, and mental component summary of quality of life had mean scores of 43.80 ± 27.88, 45.39 ± 28.58, and 42.20 ± 28.15(mean ± SD) respectively. Walking to the health facility (AOR = 2.09; 95% CI: (1.31,3.31); using public transport (AOR = 2.58; 95% CI = 1.69–3.93); having the fear of COVID-19 (AOR = 1.46; 95% CI = 1.08–1.99); having health facility admission history during the recent pregnancy (AOR = 1.62; 95% CI = 1.08–2.44); having postpartum depression (PPD) (AOR = 2.13; 95% CI = 1.57–2.89) were predictors of a lower level of overall HRQOL among postpartum women. Conclusion: The study found that nearly half of postpartum women in Ethiopia have lower HRQOL, with factors such as transport use, recent baby's pregnancy admission history, and postpartum depression (PPD) significantly affecting their overall, physical, and mental HRQOL. Fear of COVID-19 was found to be significantly associated with lower overall and physical HRQO. The implementation of appropriate strategies addressing identified factors is crucial for enhancing the HRQOL among postpartum women in Ethiopia.